Pengaruh Lokasi dan Kualitas Pelayanan Terhadap Loyalitas Konsumen pada Fotocopy Anugrah Rengat - Hermanto Hermanto; Roky Apriansyah; Khusnul Fikri; Albetris Albetris (Universitas Batanghari Jambi, 2019)
This research was conducted on AnugrahPhotocopy in Rengat with the aim to determine the effect of Location and Service Quality to Consumer Loyalty atRengatPhotocopy in Rengat. Sampling was done by random sampling method with 98 samples as respondents. The analytical method used is a quantitative descriptive method, data analysis with partially and simultaneously act (multiple linear regression analysis with the help of the IBM SPSS Stastic program version 21.0). From the results of the research, obtained a regression equation that is Y = 9,881 + 0,243X1 + 0,321X2, it can be seen that Location and Service Quality has a positive influence to Consumer Loyalty atAnugrahPhotocopy in Rengat. In addition, simultaneous testing (Test F), has been obtained F count> F table that is equal to 6.311> 3.09. So that the two independent variables namely location and service quality together have a positive and significant effect on the dependent variable, namely Consumer Loyalty atAnugrahPhotocopy in Rengat. While the Partial Regression Test (t test) shows that location variables significantly influence to Consumer Loyalty at Anugrah Photocopyin Rengat, t arithmetic> t table of 2.554> 1.98525. Variable service quality is more dominant significant effect to Consumer Loyalty at Anugrah Photocopyin Rengat namely t arithmetic> t table of 3.447> 1.98525. In addition, the results of the multiple correlation coefficient is 0.742 which shows the level of relationship between all independent variables to the dependent variable in this research is in the criteria of high relationship closeness. The magnitude of the effect caused by these three variables together affect the consumer loyalty variable with a percentage of 55.1%. While 44.9% is influenced by other factors not included in this study.